Platelet-Rich plasma in athletics: a promising therapeutic concept? - Bermon, S. (New Studies in Athletics, 2010)
The use of autologous blood-derived growth factors and particularly platelet-rich plasma are gaining popularity among professional athletes and sports physicians. This innovative therapeutic concept relies on the use of various growth factors than can be obtained in high amount after centrifugation of the patient`s whole blood.